Propriedades estruturais, eletrônicas, ópticas e vibracionais do cristal de ureia sob formalismo DFT - Silva, Bruno Poti e (2014)
Urea, [CO(NH2)2], was the first organic compound artificially synthesized in 1828 by Friedrich Whoeler. Since then, have been widely studied in various fields as nonlinear optics, protein denaturation and so on. The presence of electronegative atoms in the urea molecule, Oxygen and Nitrogen, in the carboxyl and amine groups, makes it possesses great capacity of formation hydrogen bonds, enabling the formation of complexes networks of urea molecules. The ability to formation hydrogen bonds causes that urea interacts strongly with water. Several studies have tried to explain the effect of urea in the water structure. Due interesting properties of urea crystals in the nonlinear optics, scientists have calculated, using various methods of first principle calculations, the properties of the urea crystals. The first theoretical calculation done on the urea crystal properties was made by Dovesi {it et al.} In the present work, the studies convergence were made using GGA and LDA functionals of exchange-correlation and dispersion corrections to urea crystal, which has symmetry tetragonal and spacial group P-421m. The study of energies cutoff for convergence of the crystal was done. With this evaluation of the study of the convergence, showed that the functional that described the geometrical parameters of the urea crystal was the GGA+TS. The study of electronic, optical and vibrational properties was also conducted. The energy gap obtained to the urea crystal was 5.12 eV, which is in good agreement with experimental result, obtained by optical absorption, 5.85 eV, an error of -0.63 eV (-11{%}). The effective mass calculations along differents pathways in the crystal, and using differents exchange-correlation functionals, proved to be consistent when results are compared between the functionals, obtained an maximum error of 10({%}). The infrared spectra obtained both crystal and the molecule of urea showed excellent agreement with data reported in the literature. In this work also calculated, using DFT, the Raman spectra of urea crystal in different pressure values, 0.0, 0.2, 0.4, 0.6 e 0.8 GPa. The results showed that the bands presents in lower wavenumbers are more sensitive to application of pressure to the crystal, having the ocurrence of a blue shift in these, which can be characterized an atomic rearrangement in the crystal of urea.